Pengaruh Variasi Frekuensi terhadap Nilai Kapasitansi dan Konduktansi Nanofiber Polianilin - Rajabiah, Nurlaila; Nugroho, Eko; Umiyati, Ngurah Ayu Ketut (TURBO [Tulisan Riset Berbasis Online], 2024)
This research is driven by the need to develop conductive materials that can be applied to sensitive and responsive sensors. Polyaniline-based sensors offer potential solutions for a variety of applications, including gas detection, medical imaging, and environmental monitoring. However, to optimise sensor performance, a deep understanding of the factors influencing polyaniline conductance is required. The object of this research is the synthesis of polyaniline nanofibers using the interfacial polymerization method with frequency variations. Capacitance and conductance testing uses inductance, capacitance, and resistance measuring instruments (LCR meters). The characterization results show that variations in voltage frequency have a significant impact on the conductive and capacitive properties of the nanofiber. An increase in frequency causes a decrease in capacitance at high frequencies. The highest capacitance value is at a frequency of 1 kHz, namely 149.9 pF, while the highest conductance value is at a frequency of 100 kHz, namely 134.64 siemens (1/ohm). The conductivity of polyaniline nanofiber shows a positive influence, with increasing conductance values at higher frequencies. This increase shows that the size and morphology of the nanofiber indicate the nanofiber's ability to conduct electric current. These results provide deep insight into the influence of frequency in controlling the conductive properties of polyaniline nanofibers, which can be applied in the development of sensors, flexible electronic devices, and other fields that utilise polymer conductivity. Key words: frequency, capacitance, conductance, polyaniline nanofiber.